2007
DOI: 10.1016/j.febslet.2007.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Locked 5Zs‐biliverdin blocks the Meta‐RA to Meta‐RC transition in the functional cycle of bacteriophytochrome Agp1

Abstract: The bacteriophytochrome Agp1 was reconstituted with a locked 5Zs-biliverdin in which the C 4 ‚C 5 and C 5 -C 6 bonds of the methine bridge between rings A and B are fixed in the Z and syn configuration/conformation, respectively. In Agp1-5Zs the photoconversion proceeds via the Lumi-R intermediate to Meta-R A , but the following millisecond-transition to Meta-R C is blocked. Consistently, no transient proton release was detected. The photoconversion of Agp1-5Zs is apparently arrested in a Meta-R A -like interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 21 publications
6
31
0
Order By: Relevance
“…These changes clearly occur in the subsequent transitions reflecting the Meta-R A to Meta-R C and the Meta-R C to P fr transitions, respectively. In an adduct of Agp1 with a locked 5Zs-BV chromophore the Meta-R A to Meta-R C transition was inhibited (36). The present results provide further evidence for conformational changes of the A-B methine bridge during the Meta-R A to Meta-R C transition.…”
Section: Mechanism Of Probe Attachment and Chromophoresupporting
confidence: 62%
See 2 more Smart Citations
“…These changes clearly occur in the subsequent transitions reflecting the Meta-R A to Meta-R C and the Meta-R C to P fr transitions, respectively. In an adduct of Agp1 with a locked 5Zs-BV chromophore the Meta-R A to Meta-R C transition was inhibited (36). The present results provide further evidence for conformational changes of the A-B methine bridge during the Meta-R A to Meta-R C transition.…”
Section: Mechanism Of Probe Attachment and Chromophoresupporting
confidence: 62%
“…The present results do not allow discrimination between these two possibilities. One possible scenario could be that the postulated syn to anti rotation of the C5-C6 single bond (33,36) is associated with a relocation of pyrrole ring A allowing the probe to occupy the initial position of ring A. Alternatively, a partial rotation of ring A could produce a cavity such that the probe slips beneath. These rearrangements could occur for example in the proposed hula-twist motion at C5 that involves a concerted syn to anti rotation and Z to E isomerization (33,58).…”
Section: Mechanism Of Probe Attachment and Chromophorementioning
confidence: 99%
See 1 more Smart Citation
“…The chromophore of the Agp1-M15-D197A mutant is only partially protonated at the slightly basic pH used here, whereas in wild type Agp1 the chromophore is completely protonated under these conditions (57). Because the excitation and emission spectra of 15Za-Agp1-M15-D197A are remarkably similar to those of 15Za-Agp1, we propose that fluorescence is related to the protonated chromophore.…”
Section: Discussionmentioning
confidence: 69%
“…For PCB, we have shown that the CD sign of the red transition arises from the facial disposition of the D-ring (22). CD spectra of phytobilin-and BV-containing phytochromes in their P r states share strong negative rotation for the red absorbance band (22)(23)(24)(25). This band exhibits weakly negative rotation in the P fr state of the BphP Agp1 assembled with a synthetic chromophore (25), consistent with structural results suggesting that the D-ring remains ␣-facial during P r /P fr interconversion of biliverdin phytochromes (8,16,18).…”
mentioning
confidence: 99%